Exploring Urban Agriculture’s Impact on Ecosystem Services and Beneficiary Characteristics - Sreedaya, G. S.; Kumar, R. Ajith; Shaji, Archana T; Mathew, Riza (Journal of Agricultural Extension Management, 2023)
Urban agricultural systems can contribute to the health of the natural ecology and offer more ecosystem services than they demand. Restructuring agriculture, particularly urban agriculture, as a component of a greener infrastructure system might lead to the creation of a network of agricultural systems that enhance the health of the local ecosystem by supplying ecosystem services and avoiding harmful externalities. cities could gain largely from the ecosystem services of urban agriculture in terms of environmental and socioeconomic benefits, such as water regulation, enhanced food security, or improved air quality. Urban agriculture has indeed been proposed as a means for delivering ecosystem services like benefits for mental health and cultural enrichment. Ecosystem services are often grouped into four categories: provisioning services example food and fiber, regulating services example climate regulation, and erosion control, supporting services of soil formation, oxygen production), and cultural services example recreational and health benefits. (Millennium Ecosystem Assessment, 2005). This study was conducted in Thiruvananthapuram corporation, the Capital of Kerala, to delineate the ecosystem services provided by urban agriculture as perceived by the citizens of Thiruvananthapuram corporation. Evaluation of the ecosystem services and suggesting suitable strategies for urban planners are the other objectives. 390 randomly selected respondents from 32 wards of Thiruvananthapuram corporation became part of the study. Data was collected through a pretested questionnaire and measured in the Likert Scale. The analytical tools are principal component analysis, mean, percentage, and correlation